Anglo-Catholic in religion T.S. Eliot and Christianity - Spurr, Barry (Cambridge : Lutterworth Press, 2010)
Barry Spurr's eagerly-awaited, definitive study of T.S. Eliot's Anglo-Catholic belief and practice shows how the poet's religion shaped his life and work for almost forty years, until his death in 1965. The author examines Eliot's formal adoption of Anglo-Catholicism, in 1927, as the culmination of his intellectual, cultural, artistic, spiritual and personal development to that point. This book presents the first detailed analysis of the unique influence that Anglo-Catholicism's doctrinal and devotional principles, and its social teaching, had on Eliot's poetry, plays, prose and personal life.
The sources of faith, familial and philosophical (1888-1917) -- Towards Anglo-Catholicism (1917-1927) -- The struggle for existence (1915-1933) -- Anglo-Catholicism: 'entre deux guerres' (1918-1939) -- Anglo-Catholic in religion (1927-1965) -- A Christian state -- Anglo-Catholic in literature.
Includes bibliographical references (pages 307-314) and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Eliot, T. S. -- 1888-1965 -- Religion; Eliot, T. S. -- 1888-1965 -- Ethics; Eliot, T. S. -- 1888-1965 -- Criticism and interpretation; Church of England; Eliot, T. S. -- 1888-1965; Church of England; Anglo-Catholicism.; Christianity; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; POETRY -- English, Irish, Scottish, Welsh; Anglo-Catholicism.; Christianity; Ethics; Religion; Anglo-Catholicism.; Christianity; Church of England; Eliot, T. S. -- (Thomas Stearns), -- 1888-1965 -- Criticism and interpretation; Eliot, T. S. -- (Thomas Stearns), -- 1888-1965 -- Ethics; Eliot, T. S. -- (Thomas Stearns), -- 1888-1965 -- Religion; RELIGION / History; Electronic books; Criticism, interpretation, etc